2020
DOI: 10.3832/ifor3059-013
|View full text |Cite
|
Sign up to set email alerts
|

Soil water deficit as a tool to measure water stress and inform silvicultural management in the Cape Forest Regions, South Africa

Abstract: Biogeosciences and Forestry Biogeosciences and ForestrySoil water deficit as a tool to measure water stress and inform silvicultural management in the Cape Forest Regions, South Africa Gerhardus Petrus Scheepers, Ben du Toit An understanding of variations in water availability to plantation forests on a spatial and temporal scale is essential when designing risk averse and site-specific silvicultural management regimes. Various indices of site water availability were compared to each other and to an independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Sewerniak (2020) found that productivity estimates that included soil variables were only important for nutrient‐poor soils, in this case podzols, for Scots pine in Central Europe. Scheepers and Du Toit (2020) suggested that only the soil parameters that related to water availability contributed significantly to explain forest productivity for an arid region of South Africa. Pinno and Bélanger (2011) highlighted that specific soil properties contributed to explaining the productivity of aspen trees in Canada, but that these properties varied with soil type.…”
Section: Resultsmentioning
confidence: 99%
“…Sewerniak (2020) found that productivity estimates that included soil variables were only important for nutrient‐poor soils, in this case podzols, for Scots pine in Central Europe. Scheepers and Du Toit (2020) suggested that only the soil parameters that related to water availability contributed significantly to explain forest productivity for an arid region of South Africa. Pinno and Bélanger (2011) highlighted that specific soil properties contributed to explaining the productivity of aspen trees in Canada, but that these properties varied with soil type.…”
Section: Resultsmentioning
confidence: 99%
“…The water deficit (after Thorntwaite and Mather 1955) averages 258 mm per year. In the context of plantation forest sites of the Western Cape, this value represents a high annual water deficit (Scheepers and du Toit 2020).…”
Section: Materials and Samplingmentioning
confidence: 99%